Visual evoked potentials in phenylketonuria: association with brain MRI, dietary state, and IQ. Issue 3 (September 1995) - Jones, S J; Turano, G; Kriss, A; Shawkat, F; Kendall, B; Thompson, A J
Abstract : At separate institutions, pattern reversal visual evoked potentials (VEPs) were recorded in children and older patients with phenylketonuria and compared with MRI of the brain. In nine patients aged less than 14 years, who were still on a diet low in phenylalanine, VEPs were clearly abnormal in only one and the abnormalities seen on MRI were mild. In 27 patients aged 14-31 years VEPs were abnormal in more than 80%, with significant reduction of amplitude and prolongation of latency despite the general absence of visual symptoms and abnormalities on routine neuro-ophthalmological examination. Among the older patients there was no significant correlation between VEP measures and plasma phenylalanine or tyrosine concentrations; neither was the incidence of VEP abnormalities dependent on whether or not the patients were still on a low phenylalanine diet. Some VEP amplitude measures were inversely correlated with the MRI lesion score, perhaps reflecting the severity of white matter abnormalities in the parieto-occipital region. In the older patients the amplitude of VEPs to stimulation of the central 8 degrees of the visual field was significantly correlated with IQ. The study confirms the high incidence of subclinical visual pathway involvement in older children and adults with phenylketonuria, and suggests the possibility of a link between the abnormal appearance of subcortical white matter on MRI and a physiological index of function of the CNS. As there was no evidence of general intellectual decline, it is suggested that the correlation between central field VEP amplitude and IQ may reflect abnormal development during infancy. Abnormalities on MRI, on the other hand, seem to be more closely related to current dietary state and phenylalanine concentration.